HUBUNGAN KADAR HEMOGLOBIN DENGAN PERTUMBUHAN PADA BALITA STUNTING DAN WASTING - Hestiasih Nirwanto; Tri Sunarsih; Yuli Astuti (Program Studi S1 & DIII-Kebidanan Universitas Imelda Medan, 2022)
The problem of unfulfilled nutrition is a case that is still found in Indonesia, toddlers are a group that is vulnerable to malnutrition, one of which is toddlers experiencing stunting. One of the nutrients needed is iron, this substance plays an important role in the process of neurotransmitter synthesis and myelination of neurons. Therefore, children who experience stunting have a 2.7 times greater risk of experiencing anemia. The method used is quantitative analytic, with a cross sectional design. The sample is 25 toddlers using non-probability sampling technique. Instrument in the form of a questionnaire. The data obtained are primary data and based on measurement scale variables using interval, ordinal, and nominal, then the data analysis used is univariate and bivariate analysis using the Chi-square test which is processed using SPSS 25. A rhesus positive by 36%. The most gender is male by 76%. The respondent's height is more dominantly short by 56%. The respondent's body weight is more dominantly normal by 72%. The most common age group is the range of 35 months by 28%. The most dominant educational status of parents is secondary education by 56%. The job status of the respondent's father is mostly laborer (40%) and the respondent's mother is a housewife (92%). Based on family income per month, the most respondents are income of Rp. 1,900,000 month, with a percentage of 80%. The results of the Chi Square Test showed that the P value was 0.0891 so it was found that the H0 value was rejected because the p value was 0.005, which means that there is no relationship between hemoglobin levels and the incidence of stunting growth in toddlers in Ngalang Village, Gunung Kidul. The incidence of stunting in toddlers shows that there is no significant relationship between hemoglobin levels and the growth of stunting toddlers.